Sedal trans-hepatic choledocostomy: Its use in liver trauma - Balboa, Oscar; Bertullo, Hugo; Voelker, Ricardo; Lerena, Ana; Perdomo, Roberto (Cirugía del Uruguay, 1979)
The use of seton transhepatic choledocostomies is suggested far cases of traumatic lesion of segmentary glissonian pedicles. This pro·cedure is of considerable value in control of bilirrhage.